An immunohistochemical study of primary signet-ring cell carcinoma of the stomach and colorectum: III. expressions of EMA, CEA, CA19-9, CDX-2, p53, Ki-67 antigen, TTF-1, vimentin, and p63 in normal mucosa and in 42 cases - Terada, Tadashi (e-Century Publishing Corporation, 2013)
There have no comprehensive immunohistochemical studies of primary signet ring cell carcinoma (SRCC) in the stomach and colorectum. The author examined the expression of nine common antigens (EMA, CEA, CA19-9, CDX-2, p53, Ki-67 antigen, TTF-1, vimentin, and p63) in the non-tumorous normal epithelium of the stomach and colorectum and in 42 cases of primary SRCC of the stomach (30 cases) and colorectum (12 cases). The normal epithelium of the stomach and colon consistently (100%) expressed EMA, CEA, CA19-9, CDX-2, and Ki-67 (labeling <15%). Normal epithelium of these locations never expressed p53, TTF-1, vimentin, and p63. In the primary gastric SRCC, the expression percentage of EMA was 57% (17/30), CEA 100% (30/30), CA19-9 100% (30/30), CDX-2 43% (13/30), p53 83% (25/30), Ki-67 100% (30/30) (labeling index= 36 ± 23 %), TTF-1 0% (0/30), vimentin 0% (0/30), and p63 0% (0/30). In primary colorectal SRCC, the expression percentage of EMA was 25% (3/12), CEA 100% (12/12), CA19-9 100% (12/12), CDX-2 93% (28/30), p53 75% (9/12), Ki-67 100% (30/30) (labeling index= 47% ± 26 %), TTF-1 0% (0/12), vimentin 0% (0/12), and p63 0% (0/12). A comparative statistical analysis showed significant difference in EMA (gastric SRCC 57% vs colorectal SRCC 25%) and CDX-2 (43% vs 93%). There were no significant differences in the other seven antigens’ expression between primary gastric SRCC and primary colorectal SRCC. These findings provide much knowledge of primary SRCC of the stomach and colorectum. The data indicated primary gastric SRCC frequently express EMA but not CDX-2 whereas primary colorectal SRCC frequently express CDX-2 but not EMA. These findings also suggest that EMA and CDX-2 are down-regulated during the gastric SRCC carcinogenesis. This down regulations may be associated with the malignant transformation of gastric SRCC. The data of colorectal SRCC suggest EMA is markedly down-regulated and also suggest that this EMA down-regulation may be associated with the carcinogenesis of colorectal SRCC. The expression pattern of EMA and CDX-2 may be useful in differential diagnosis between primary gastric SRCC and primary colorectal SRCC in the metastatic sites of SRCC.